Neuropsychological pattern during gluten free diet (GFD) in elderly coeliac patients. (13th March 2011) - Casella, S; Zanini, B; Lanzarotto, F; Caselani, F; Magni, A; Romanelli, G; Lanzini, A
Abstract : Introduction: Previous studies suggested a correlation between celiac disease (CD) and cognitive impairment, but only few described these characteristics in the elderly, all based on a small number of patients or as case-reports. Methods: The aim of this study was to analyze the neuropsychological pattern in CD patients aged ≤ 65 years by comparison with a population of patients with GI disorders different than CD. We retrospectively identified a cohort of CD elderly patients attending our CD Clinic, all on GFD for a minimum of 12 months (n=18 Group A). We also identified sex and age matched (±5 years) control patients (n=18 Group B). Patients and controls were submitted to neuropsychological tests including: BADL (Basic Activity Daily Living); IADL (Instrumental Activity Daily Living); Barthel Index; GDS (Geriatric Depression Scale); MMSE (Mini Mental Test Examination); Trail Making Test (TMT A, B, B-A); Raven's matrices; Digit Symbol; Semantic and Phonemic fluency; Rey list; Verbal Span; Ideomotor and Buccofacial apraxia. Results: There were no significant differences of laboratory parameters, thyroid profile, vitamin B12 and folate level in the two groups and all the patients were TPHA negative. The differences of neuropsychological tests between the two cohorts are summarised in table 1 . All tests indicated that cognitive performances were worse (except for Rey list) in group A than group B. Conclusion: CD elderly patients have worse cognitive performance than sex and age-matched subjects, despite being on GFD for a minimum of 12 months. The attention deficiency, semantic fluency, visuo-spatial, executive ability impairment and ideo-motor apraxia is likely to be related to thalamic, frontosubcortical, frontotemporal and cerebellar impairment. The neuropsychological pattern of elderly CD celiac patients on GFD has the characteristics of vascular cognitive impairment.